2004
DOI: 10.1111/j.1398-9995.2005.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy for allergic rhinitis: systematic review and meta‐analysis*

Abstract: Allergic rhinitis is a common condition which, at its most severe, can significantly impair quality of life despite optimal treatment with antihistamines and topical nasal corticosteroids. Allergen injection immunotherapy significantly reduces symptoms and medication requirements in allergic rhinitis but its use is limited by the possibility of severe systemic reactions. There has therefore been considerable interest in alternative routes for delivery of allergen immunotherapy, particularly the sublingual rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
457
0
17

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(497 citation statements)
references
References 23 publications
18
457
0
17
Order By: Relevance
“…Comparisons of skin biopsies from the subcutaneous injection sites 142 and the oral mucosa 143 of SLIT-treated allergic subjects confirmed the negligible presence of inflammatory cells. 144 In addition, the high doses administered with oral immunotherapy resulted in significant local reactions, including gastrointestinal bleeding, which were possibly able to interfere with antigen absorption and thus with immunization.…”
Section: Oralmentioning
confidence: 60%
See 1 more Smart Citation
“…Comparisons of skin biopsies from the subcutaneous injection sites 142 and the oral mucosa 143 of SLIT-treated allergic subjects confirmed the negligible presence of inflammatory cells. 144 In addition, the high doses administered with oral immunotherapy resulted in significant local reactions, including gastrointestinal bleeding, which were possibly able to interfere with antigen absorption and thus with immunization.…”
Section: Oralmentioning
confidence: 60%
“…145 Clinically, use of the sublingual route is supported by numerous controlled trials showing its efficacy in asthma and rhinitis in adults and children. 143,146 Additionally, no severe adverse events occurred during the trial, and the most common adverse events were mild asthma attack and local rash. Cao et al evaluated the safety and efficacy of SLIT with Der f drops in Der f allergic asthma and/or rhinitis patients.…”
Section: Oralmentioning
confidence: 96%
“…It is clear, looking at the published articles that SLIT is clinically effective [7]. It is also clear that there is a large heterogeneity among studies, mainly due to the variability in the inclusion criteria, dose of allergen, duration, methodological aspects, and reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have clearly shown a dose-dependent effect of SLIT [5,6], indicating robust support in favor of its clinical efficacy. Due to the large number of trials available, several meta-analyses have been carried out (Table 1), with various inclusion criteria such as rhinitis and asthma [7,8], asthma only [9], asthma and/or rhinitis in children [10,11], conjunctivitis [12]. Moreover, separate meta-analyses for single allergens such as dust mite [13] or grasses [14] have also been published, with favorable results as well.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the nature, quantity and quality of research evidence (essentially efficacy and safety) and patient values [quality of life (QoL) and treatment satisfaction] in DBPC RCTs. We did not seek to define the efficacy and safety of SIT itself or directly compare SCIT and SLIT, because these topics have been examined and discussed elsewhere (9)(10)(11)(12)(13)(14).…”
Section: -434mentioning
confidence: 99%